1988
DOI: 10.1042/bj2500179
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surgical stress and short-term fasting on protein synthesis in vivo in diverse tissues of the mature rat

Abstract: 1. We measured fractional rates of protein synthesis, capacities for protein synthesis (i.e. RNA/protein ratio) and efficiencies of protein synthesis (i.e. protein-synthesis rate relative to RNA content) in fasted (24 or 48 h) or fasted/surgically stressed female adult rats. 2. Of the 15 tissues studied, fasting caused decreases in protein content in the liver, gastrointestinal tract, heart, spleen and tibia. There was no detectable decrease in the protein content of the skeletal muscles studied. 3. Fractional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 31 publications
2
57
1
Order By: Relevance
“…The effects of fasting on hepatic protein synthesis in the suckling rats in our study were qualitatively similar to those reported in adult and young weaned rats (8)(9)(10). We found quantitative differences, however, depending on the stage of development.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The effects of fasting on hepatic protein synthesis in the suckling rats in our study were qualitatively similar to those reported in adult and young weaned rats (8)(9)(10). We found quantitative differences, however, depending on the stage of development.…”
Section: Methodssupporting
confidence: 75%
“…A short-term fast (24 h) in young growing and adult rats reduces the hepatic protein synthesis rate and protein mass by approximately 30 and 20%, respectively (8)(9)(10). Alternatively, in skeletal muscle, reduced protein synthesis in response to a short-term fast is greater in young rats than in older weaned rats (1 1, 12).…”
mentioning
confidence: 99%
“…We chose to study nucleic acids because they are closely linked to the production of body mass and appear to change at a time frame of interest for studying species interactions (Foster 1990, Schlechtriem et al 2008 Growth rate and protein synthesis rates are often correlated with RNA content, or ratios of RNA:DNA and RNA:protein in both vertebrates and invertebrates (Buckley 1979, Houlihan et al 1993, Dahlhoff & Menge 1996, Bergeron 1997, Saiz et al 1998, Wagner et al 2001. While ribosomes, which are composed largely of ribosomal RNA (rRNA), set the upper capacity for protein synthesis, the actual rate will vary with translational efficiency depending on short-term needs (Millward et al 1973, Preedy et al 1988. In order to make comparisons between groups, total RNA must be normalized to a single cell or to body size, usually expressed as total DNA or protein; hence the frequent use of the ratios RNA:DNA and RNA:protein.…”
Section: Introductionmentioning
confidence: 99%
“…Thus over the past 3 decades, RD has been widely used as an index of nutritional condition (Clemmesen 1994, Grønkjaer et al 1997, Buckley et al 1999, St. John et al 2001) and, to a lesser extent, as a means to estimate weight-specific growth rate (G) in fish larvae (Buckley 1984, Caldarone et al 2003, Caldarone 2005, Malzahn et al 2007. Since the actual rate of translation (protein synthesis per unit RNA) varies with temperature (Millward et al 1973, Preedy et al 1988, Farewell & Neidhardt 1998, estimating G from RD in ectotherms requires an adjustment for the activity of RNA due to temperature. Ideally, laboratory experiments conducted at different feeding levels and water temperatures are used to define the relationship among RD, temperature (T) and G (RD-T-G relationship).…”
Section: Introductionmentioning
confidence: 99%